Implementasi REST API Pada Sistem Informasi Tempat Wisata di Yogyakarta Berbasis Android - Azel Aldi Saputra; Sutarman (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Yogyakarta is a city that has many tourist attractions to date. The large number of tourist attractions makes it difficult for tourists to find tourist attractions due to insufficient information. This research aims to create an information system for tourist attractions in Yogyakarta so that tourists can easily find tourist information. The benefit of this research is that tourism information data can be well structured in a system. This research uses the waterfall method, which includes six stages of development. The technology used is REST Api, which can enable data exchange between the database and the system to be more flexible and reduce the load on the application. This research will produce two mutually integrated systems, namely a website and an application. Testing of this system was carried out using a black box testing approach involving several tourists. The results obtained from this test are that tourists can easily search for tourist information so that tourism in Yogyakarta is not focused on a tourist attraction.